Biotransformation of metribuzin under various electron acceptor conditions. Issue 1 (8th April 2022) - Phillips, Thomas; Boopathy, Raj
Abstract: Metribuzin is a triazine herbicide used in sugarcane fields to control broadleaf weeds. Metribuzin that is washed into waterways as runoff can be linked to hermaphroditism in frogs as well as algal and macrophyte death. Metribuzin degradation by bacteria is essential to reduce the half‐life of metribuzin in the environment. The objective of this study was to determine metribuzin degradation by various bacterial consortia developed from a sludge collected from a sewage treatment plant. The sludge was exposed to metribuzin under various electron acceptor conditions including, nitrate reducing, sulfate reducing, and mixed electron acceptor conditions. Results showed metribuzin was removed significantly under mixed electron acceptor condition when glucose served as a co‐substrate followed by sulfate reducing and nitrate reducing conditions. The major metabolites identified in metribuzin degradation were desamino‐metribuzin, diketo‐metribuzin, and desamino‐diketo‐metribuzin. Repeated exposure to metribuzin may help the bacteria to adapt and evolve metribuzin degrading enzymes.